Reflections from a hospital chaplain - Reek, Jennifer (International journal for the study of the Christian church, 2024)
Jennifer Reek works at a hospital in the American Southwest. The hospital serves varied cultures: Native American, Hispanic, white, and various combinations of those, with an intriguing mix of religious and spiritual practice. The following reflections, on her experiences as a hospital chaplain over the past several years, are at the invitation of her former thesis advisor and now friend of many years, David Jasper. They are an adaptation of weekly reflections submitted over a year and a half of Clinical Pastoral Education training.